Customer Satisfaction Towards ATM Service In Nepalese Banking Sector - Goet, Joginder (Management Dynamics, 2020)
This research is intended to examine the relationship between reasonability of fee charged, choice of ATM, usage of service and post purchase behavior and customer satisfaction. The research has used primary sources of data. A well-structured questionnaire was designed to collect data from 200 respondents using purposive sampling technique. The data was analyzed using correlation. The findings revealed that there was a positive and significant relationship between reasonability of fee charged, choice of ATM, usage of service and post purchase behavior and customer satisfaction. The research is afresh study in the field of banking sector in Nepalese context. There is an implication of research in the banking sector.